Age‐Related Outcomes of Valve‐in‐Valve Transcatheter Aortic Valve Replacement for Structural Valve Deterioration - Takashi Nagasaka; Vivek Patel; Kazuki Suruga; Alon Shechter; Ofir Koren; Tarun Chakravarty; Wen Cheng; Hideki Ishii; Hasan Jilaihawi; Mamoo Nakamura; Raj R. Makkar (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Valve‐in‐valve transcatheter aortic valve replacement (TAVR) is a recognized alternative for treating the structural valve deterioration of bioprosthetic valves. Recent guidelines and trials have expanded the indications for TAVR to include younger patients with structural valve deterioration. In this study, we aimed to examine the outcomes of valve‐in‐valve TAVR across different age groups to understand the age‐related clinical outcomes of treating structural valve deterioration following surgical aortic valve replacement and TAVR. Methods and Results In this retrospective study, we included patients who underwent valve‐in‐valve TAVR at our center. We compared procedural complications and clinical outcomes among patients <75 years of age (n=99), those 75 to 84 years of age (n=103), and those ≥85 years of age (n=71). Echocardiography and computed tomography were used for follow‐up evaluations. This study included 273 patients and revealed a low in‐hospital complication rate across all age groups. Although the 3‐year risk of all‐cause mortality was higher in patients >85 years of age, no significant differences in the incidence of stroke/transient ischemic attack were observed among age groups. All groups exhibited significant improvements in valve hemodynamics that persisted for 3 years. Although leaflet thrombosis assessed using computed tomography imaging 30 days post‐TAVR was more prevalent in the older group, age was not an independent predictor of this outcome. Conclusions Valve‐in‐valve TAVR was associated with an increased 3‐year mortality risk among older patients despite consistent hemodynamic benefits across all age groups. Age‐related differences in leaflet thrombosis did not predict hypoattenuated leaflet thickening, indicating that further studies are necessary to elucidate its implications.